Analysis of conditions and vulnerability of mangrove ecosystem degradation in Dumai City Riau Province Indonesia - Tyas Dita Pramesthy; Perdana Putra Kelana; Djunaidi Djunaidi; Muhammad Nur Arkham; Rangga Bayu Kusuma Haris (JURNAL PERIKANAN DAN KELAUTAN, 2022)
There is still minimum information on the condition of the mangrove ecosystem, such as canopy cover and vulnerability of the ecosystem. Therefore, it was necessary to analyze that by assessing the Important Value Index (INP), canopy cover and vulnerability to degradation. The primary data needed are the type, density, frequency and basal area of mangroves obtained by the Transect Line Plot (TLP) method. The canopy cover was obtained using the Hemispherical Photography method. The data analyzed using INP, pixel analysis with binary images and compared to standard criteria of mangrove damage and vulnerability to degradation of mangrove ecosystems. This study identified 5 types of mangroves, Avicennia alba, Rhizophora apiculata, Rhizophora mucronata, Xylocarpus granatum and Sonneratia alba. Xylocarpus granatum was the species with the highest INP at stations 1 and 2, while at station 3 it was Avicennia alba. Station 1 has the highest canopy cover with a value of 86%. The condition of the mangrove ecosystem in Dumai is generally in the good category with medium stands. In addition, the level of vulnerability to mangrove degradation in can be categorized as low vulnerability. Although this research was conducted with simple methods and equipment, the results can provide an overall illustration of the condition of the Dumai’s mangrove ecosystem, making it easier for interested parties to manage the ecosystem.